2015
DOI: 10.1590/0004-282x20150029
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor signs in Parkinson’s disease: a review

Abstract: The traditional pathological description of PD as a pre-synaptic degenerative process affecting dopaminergic neurons in the substantia nigra pars compacta (SNc) of the midbrain with formation of Lewy bodies (LB) has changed dramatically in the last decade since functional and neuropathological studies showed the occurrence of extensive extranigral involvement 1 . Among these investigations, the seminal study of Braak et al. 2 suggested that the degenerative process in the PD starts in the caudal regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
15

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 59 publications
(81 reference statements)
0
54
0
15
Order By: Relevance
“…In this sense, it is suggested that in our study the total PDQ-39 score decreased significantly, mainly due to the observed decrease in the mobility domain score. In addition, the intervention was effective for two domains related to physical aspects (mobility and bodily discomfort) commonly affected in PD (28) and for a non-motor symptom (emotional well-being), which usually plays an important role in the functionality and QoL (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is suggested that in our study the total PDQ-39 score decreased significantly, mainly due to the observed decrease in the mobility domain score. In addition, the intervention was effective for two domains related to physical aspects (mobility and bodily discomfort) commonly affected in PD (28) and for a non-motor symptom (emotional well-being), which usually plays an important role in the functionality and QoL (1).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a progressive neurodegenerative disease associated with motor, cognitive, behavioral and social repercussions (1,2). These can imply loss of autonomy and independence of the individual, negatively influencing their quality of life (QoL) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…RBD has been reportedly present in 42-58% of all IPD patients. Patients with RBD have a 65% risk of development of IPD in the next ten years, making RBD specific clinical marker for premotor IPD 8,19 . In the present study, consistent with the literature, the rate of RBD was found to be 51.5%, which is compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PD patients may present with a variety of motor and non-motor signs and symptoms that are considered uncommon or rare 1,3,4,5 . The motor signs in this series included tremor with an unusual presentation reported by three patients.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty with precise description and interpretation, as well as atypical forms of tremor, pain, other modalities of sensation, and secondary signs of RA syndrome make the initial diagnosis even more challenging but may also be clues for the active pursuit of non-obvious cardinal signs of the disease. Improved after watch was switched to contralateral wrist, while on L-dopa; 3,4,5 refered by the patients as "the shirt's button sign", "wet pillow sign", and "short jacket's sleeve sign".…”
Section: Discussionmentioning
confidence: 99%